9h-2h=14

Simple and best practice solution for 9h-2h=14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9h-2h=14 equation:


Simplifying
9h + -2h = 14

Combine like terms: 9h + -2h = 7h
7h = 14

Solving
7h = 14

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Divide each side by '7'.
h = 2

Simplifying
h = 2

See similar equations:

| n^2-6n-8=0 | | 3(n+4)=4n | | 5+(-6x)=-1 | | 10d-8d=20 | | v/6-1=0 | | 12.47=s-5.52 | | 4n-5=9+2n | | 3c-2c=16 | | 63=50+C-40/4 | | y=3(9)-12 | | 2x^3-8x=5 | | 3x(15-x)=150 | | 9(n+4)=8+5n | | Axb+25=25 | | 2m+3n=6 | | 2q-q+3q-q=20 | | 3p+pq+2pr= | | 6h+8=12 | | .4+98234= | | 2x^3-8x-5=0 | | 4[2t-(3-t)+5]=4(1-x) | | 16=k/3-111 | | 6x+2x+4=3x+3-5x-9 | | 11t+2t-12t=18 | | 9h+5=16 | | 6-2(x+7)=-4x-12 | | 71.77=c+36.82 | | (x-y)*y(dx)=x^2(dy) | | 2-20f=-19f-10 | | =(5x^5+4x^4+6)-(-12x^4+8x^5-18) | | 5a-4a=14 | | 18h=20+19h |

Equations solver categories